Immunomodulatory Effects of Palladium(II) Complexes of 1,2,4-Triazole on Murine Peritoneal Macrophages - Bego, Amadeu Moura [UNESP]; Frem, Regina Célia Galvão [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Mauro, Antonio Eduardo [UNESP]; Ananias, Sandra R. [UNESP]; Carlos, Iracilda Z. [UNESP]; da Rocha, Michelle C. [UNESP] (Soc Brasileira Quimica, 2009)
The 1,2,4-triazolyl-bridged polynuclear complexes [{PdCl(2)(mu-Htrz)}(n)] (1) and [{PdBr(2)(mu-Htrz)}(n)] (2) have been obtained in this work. Compound 1 is prepared by the displacement of acetonitrile from [PdCl(2)(MeCN)(2)] by 1,2,4-triazole (Htrz). Further addition of potassium bromide to the reaction medium afforded complex 2. The new complexes have been isolated, purified and characterized by means of elemental analysis, IR and UV-visible electronic spectroscopies and thermogravimetric (TG) curves. The experimental data suggested that, in both cases, the coordination of 1,2,4-Htrz takes place through the N(2) and N(4) atoms, bridging the palladium centers. The square-planar coordination polyhedron of palladium(II) is determined by two nitrogen atoms from the triazole ligands, while the other two coordination positions are occupied by the chloro (1) or bromo (2) ligands. TG curves indicated that the nature of the anionic ligand does not affect significantly the thermal stability of 1 and 2. The final products of the thermal decompositions were identified as metallic palladium by X-ray powder diffractometry. Preliminary tests involving the evaluation of the effects of compounds 1, 2 and Htrz on H(2)O(2) and NO production in cultures of peritoneal macrophages from BALB/c mice were carried out in vitro.
Keywords: palladium(II) complexes; 1,2,4-triazole; macrophages; nitric oxide; hydrogen peroxide